Fuzzy finite switchboard automata with complete residuated lattices - Ebas, Nur Ain; Amir Hamzah, Nor Shamsidah; Jacob, Kavikumar; Rusiman, Mohd Saifullah (Science Publishing Corporation, 2018)
The theory of fuzzy finite switchboard automata (FFSA) is introduced by the use of general algebraic structures such as complete residuated lattices in order to enhance the process ability of FFSA. We established the notion of homomorphism, strong homomorphism and reverse homomorphism and shows some of its properties. The subsystem of FFSA is studied and the set of switchboard subsystemforms a complete ℒ -sublattices is shown. The algorithm of FFSA with complete residuated lattices is given and an example is provided.